PENDAMPINGAN PEMBUATAN VIDIO ANIMASI BERBASIS BENIME BAGI GURU SDIT DARUSSALAM MEDAN - Dinda Yarshal (Universitas Islam Sumatera Utara, 2020)
Media is one that is very important in the learning process, namely as a means or device that functions as an intermediary in a communication process, so in other words the media is a tool that is anything that can be used to stimulate thoughts, feelings, attention and abilities or skills. students so that they can encourage the learning process that can be used as a forum for delivering messages to achieve teaching goals. therefore this service activity is carried out with the aim of being able to equip Darussalam SDIT teachers in making learning media, namely making animation videos based on benime. The method used in the implementation of this service activity is through the method of socialization and simulation approaches in the form of lectures and demonstrations. The results of the implementation of this service are expected that teachers already have their own products, namely in the form of learning media in the form of animated video based on animation based on the theme chosen by the teacher so that it can be used in the coming school year. In the end, the team of service implementation activities through this activity hopes that SDIT teachers, especially at SDIT Darussalam schools, can increase their knowledge and skills in presenting learning that is more attractive to students in learning.